POTENTIAL OF THREE LOCALLY AVAILABLE FERMENTED OIL CAKE PROTEIN AS REPLACEMENT OF GROUNDNUT OIL CAKE PROTEIN IN THE DIET OF ROHU, LABEO ROHITA - Mohanty, S.; CHOUDHURY, D.; SAHU, B.; KUMAR, SHIVENDRA; MOHANTA, K. N.; DAS, S. S.; BARIK, B. (Journal of the Inland Fisheries Society of India, 2026)
The study was carried out to find out the efficacy of three locally available oil cakes namely, sunflower oil cake (SFOC), linseed oil cake (LSOC) and coconut oil cake (COC) in the diet of rohu (Labeo rohita) by replacing groundnut oil cake (GNOC) in a feeding trial of 90 days. Seven iso-nitrogenous (CP 30%) and iso-caloric (365 kcal/100 g feed) experimental diets were formulated by replacing 50% of GNOC protein of the control diet (T0 ) with raw SFOC (T1 ), fermented SFOC (T2 ), raw LSOC (T3 ), fermented LSOC (T4 ), raw COC (T5 ) and fermented COC (T6 ).  At the end of the feeding trial a significantly higher (P